Mikronauczanie a kształcenie i doskonalenie kompetencji fonologicznej w nauczaniu języka francuskiego jako obcego na poziomie akademickim - Gajos, Mieczysław (Neofilolog, 2025)
Microteaching, an active teaching method developed at Stanford University in the 1960s, originally relied on advanced technological support for audio and video recording. In Poland, its use in training foreign language teachers began only in the late 1970s and early 1980s. Today, with widespread access to simple recording tools, such as smartphone cameras, it is worth re-evaluating the potential of this method for developing teaching and linguistic skills among future language educators. This article explores the application of microteaching in fostering phonological competence, particularly in improving articulation skills during French phonetics classes for foreign language learners. Research findings confirm that microteaching, combined with modern technology, can be an effective tool in professional language teacher education, promoting student autonomy and enhancing learning outcomes.